PENERAPAN BALANCED SCORECARD SEBAGAI TOLAK UKUR DALAM PENGUKURAN KINERJA USAHA BUDIDAYA IKAN LELE DI KECAMATAN KOTO TANGAH KOTA PADANG: Budidaya Ikan Lele; Balanced Scorecard; Kinerja Usaha - Imtihan Imtihan; Lisa Mayasari; Yulhendri Yulhendri (Jurnal Hilirisasi IPTEKS, 2022)
The basis for the implementation of this activity was caused that catfish farming is one of the businesses that are widely occupied by the people of Koto Tangah sub district, Padang city. The lack of knowledge and skills possessed in the effort to develop catfish farming business resulted in many efforts of farmers who suffered losses and even closed the business. The method that was used in this activity is the application of a Balanced Scorecard that was connected with the goals, strategies, and objectives in achieving a certain level of growth and obtaining competitive advantages. The implementation of the Balanced Scorecard was carried out through 4 (four) stages; namely (1) program socialization, (2) Training, (3) mentoring and (4) program Monitoring and Evaluation. From this activities, the high interest of participants in applying the Balanced Scorecard approach in order to they are able to measure their business performance. It could be seen from (1) the enthusiasm of the members in participating in program activities ranging from socialization to training provided by Team Members ; (2) based on the questionnaire that has been filled by the participants of activities also illustrates the high desire for participants to apply the Balanced Scorecard. The activity is also equipped with the provision of materials and equipment to the group of catfish farmers in Koto Tangah sub district, Padang city therefore they are able to develop a Balanced Scorecard strategy that can be used as a benchmark in measuring the business performance of activity participants.